Isu dalam Pembiayaan Perumahan: Analisis Perbandingan Produk Berasaskan Musharakah Mutanaqisah dan Konvensional (Sains Humanika, 2013)
Islamic financing products are completely different between conventional loan products. Islamic products are based on shariah concepts such as Murabahah, Bay‘ Bithaman Ajil (BBA), BBA komoditi, Ijarah Thumma Bay`, Istisna‘ and musharakah mutanaqisah (MM). While the conventional loans is based on lending. musharakah mutanaqisah (MM) is the hybrid contract based on partnership and ending with single ownership. The early of this concept applied in banking practice after year 2000. Equity-based concept is strongly encouraged its use in daily practices based on the concept of Islam as compared to debt such as Bay‘ Bithaman Ajil (BBA). Therefore, this article will analyze and comparison between the concept of products based on musharakah mutanaqisah (MM) with a conventional loan products. Focus for the comparison is about financing and housing loan products in Malaysia.
Keywords: Conventional housing Islamic home financing; musharakah mutanaqisah